Teachers AI Awareness in Science Teaching in Urban and Rural Secondary Schools in Abua-Odual LGA. Implications for Stem Education - Ayibatonye, Joseph, Endurance; Walson, Omoghoyan B.A. (Journal of Innovation in Education and Social Research, 2025)
This study examined teachers’ awareness of Artificial Intelligence (AI) in science teaching in urban and rural secondary schools in Abua-Odual Local Government Area, highlighting implications for STEM education. A descriptive survey research design was adopted to obtain information from science teachers without manipulating any variables. The population comprised all science teachers in public and private secondary schools in the area, including teachers of Biology, Chemistry, Physics, and Basic Science. Using stratified random sampling based on school location, a sample of 70 science teachers from urban and rural schools was selected. Data were collected using a researcher-developed questionnaire titled “Teachers’ AI Awareness in Science Teaching Questionnaire (TAASTQ)”. The instrument was validated by experts in Science Education, Educational Technology, and Measurement and Evaluation, while its reliability was established using the Cronbach Alpha method, yielding a coefficient of 0.82. Data were analyzed using descriptive statistics to answer the research questions and inferential statistics to test the hypotheses at the 0.05 level of significance. Findings revealed that science teachers demonstrated a moderate level of awareness of AI in science teaching. The results also showed no significant difference in AI awareness between teachers in urban and rural secondary schools. One of the recommendations made was that educational authorities should develop clear guidelines and policies that encourage the inclusion of AI in STEM education, ensuring that teachers understand how AI aligns with curriculum objectives.